UPAYA GURU MENINGKATKAN KEMAMPUAN MEMBACA DINI ANAK MELALUI PERMAINAN KARTU KATA DI RA DRUSHOLIHIN HUJUNG TAHUN PELAJARAN 2021/2022 - Deli Saputra; Krisnayanti Krisnayanti; Ratna Dewi (STIT PRINGSEWU, 2022)
This research is motivated by the low ability to read early in children. In this case most of the children have not been able to read early but only memorize it. This is indicated by the condition of the children of 31 students in group B RA Darusholihin Hujung who were able to read only 10 children at the beginning. The low ability to read early is caused by the learning methods used by teachers do not vary or are monotonous so that children experience boredom. The purpose of this research is the low ability to read early because the learning methods used by teachers do not vary or are monotonous so that children experience boredom. This research method is class action with the stages of each cycle, namely planning, implementing, observing, and reflecting. Data collection techniques in this study were carried out by means of observation and test questions. The collected data were analyzed using qualitative and quantitative analysis techniques. The results showed that the application of early reading skills in group B RA Darusholihin's children through word card activities increased. The increase in children's reading ability can be seen from the average observation results of pre-action children's reading, namely 39.13%, in the first cycle it reached 48%, in the second cycle it reached 74%. So the percentage of 74% has reached the achievement target with Very Good Developing (BSB) criteria